ANTESEDEN DARI VIRTUAL ORGANIZATIONAL COMMITMENT DAN DAMPAKNYA TERHADAP VIRTUAL CARE PERFORMANCE (STUDI PADA PLATFORM TELEMEDISIN XYZ DI INDONESIA) - Dinata, Freddy; Antonio, Ferdi (FEB Universitas Sam Ratulangi Manado, 2024)
The presence of telemedicine plays a vital role in the healthcare system of developing countries, as it can facilitate access to healthcare services, especially in remote areas. However, various factors can influence the performance of online medical advisors on telemedicine platforms. The aim of this research is to analyze the factors affecting the performance of online medical advisors on telemedicine platforms. The variables under investigation include personal innovativeness with information technology (IT), computer self-efficacy, habits, and e-leadership. These four variables will be treated as independent variables. Mediating variables consist of exploitative use of telehealth technology, virtual organizational commitment, and the dependent variable is virtual care performance, also known as virtual healthcare service performance. This research is conducted using a quantitative approach with an online questionnaire instrument. Data analysis is performed using multivariate techniques, specifically Partial Least Square-Structural Equation Modelling (PLS-SEM). The research results indicate that all four independent variables under investigation have a positive influence on virtual organizational commitment.